2020
DOI: 10.4149/av_2020_415
|View full text |Cite
|
Sign up to set email alerts
|

Variability of nonpathogenic influenza virus H5N3 under immune pressure

Abstract: Mutations arising in influenza viruses that have undergone immune pressure may promote a successful spread of mutants in nature. In order to evaluate the variability of nonpathogenic influenza virus A/duck/Moscow/4182-C/2010(H5N3) and to determine the common epitopes between it and highly pathogenic H5N1 avian influenza viruses (HPAIV), a set of escape mutants was selected due to action of MABs specific against A/chicken/Pennsylvania/8125/83(H5N2), A/Vietnam/1203/04(H5N1) and A/duck/ Novosibirsk/56/05(H5N1) vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The mouse-adapted virus A/chicken/NJ/294598-12MA/2004 (H7N2) (MA/NJ) was obtained by serial passages of the original chicken wild-type A/chicken/NJ/294598-12/2004 (H7N2) (ch/NJ) virus in the lungs of mice [ 27 ]. The MA/NJ virus was used as the initial virus to produce escape mutants that have avoided immune pressure and survived in the presence of MABs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mouse-adapted virus A/chicken/NJ/294598-12MA/2004 (H7N2) (MA/NJ) was obtained by serial passages of the original chicken wild-type A/chicken/NJ/294598-12/2004 (H7N2) (ch/NJ) virus in the lungs of mice [ 27 ]. The MA/NJ virus was used as the initial virus to produce escape mutants that have avoided immune pressure and survived in the presence of MABs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the mutations acquired in HA during the initial adaptation of the chicken influenza virus ch/NJ to mice, the MA/NJ virus acquired one in PB2, E627K [ 27 ]. All of the escape mutants characterized here have retained this mutation in PB2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings illustrate that the effects of the viral fitness for the competition among SARS‐CoV‐2 variants is not always the same. Immune pressure represents another driving factor that promotes the generation of novel variants of some pathogenic viruses 15–18 . Recently, Ravindra K Gupta confirmed that convalescent plasma treatment for immune‐suppressed individuals led to the emergence of SARS‐CoV‐2 variants with reduced susceptibility to neutralizing antibodies 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Immune pressure represents another driving factor that promotes the generation of novel variants of some pathogenic viruses. [15][16][17][18] Recently, Ravindra K Gupta confirmed that convalescent plasma treatment for immune-suppressed individuals led to the emergence of SARS-CoV-2 variants with reduced susceptibility to neutralizing antibodies. 19 However, whether immune selection pressure contributes to the emergence and displacement of SARS-CoV-2 epidemic variants lacks direct evidence.…”
mentioning
confidence: 99%